2014
DOI: 10.1073/pnas.1312099111
|View full text |Cite
|
Sign up to set email alerts
|

Chitin-induced activation of immune signaling by the rice receptor CEBiP relies on a unique sandwich-type dimerization

Abstract: Perception of microbe-associated molecular patterns (MAMPs) through pattern recognition receptors (PRRs) triggers various defense responses in plants. This MAMP-triggered immunity plays a major role in the plant resistance against various pathogens. To clarify the molecular basis of the specific recognition of chitin oligosaccharides by the rice PRR, CEBiP (chitin-elicitor binding protein), as well as the formation and activation of the receptor complex, biochemical, NMR spectroscopic, and computational studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
250
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 284 publications
(260 citation statements)
references
References 52 publications
4
250
0
1
Order By: Relevance
“…T. thus proposed a "cross-linking" model in which the two ends of long chitin oligomers each bind a LysM-ECD to form a dimer. In a separate NMR study assisted by synthetic chemistry, N-acetyl groups of alternating sugars were found to be located on two opposite sides of the chitin chain and directly bound by the LysM-ECD (Hayafune et al, 2014). Depleting N-acetyl groups from one side of the chitin chain did not affect chitin binding to a CEBiP-ECD, but abolished dimerization.…”
Section: Ligand Binding and Oligomerization Of Prr Receptor Complexesmentioning
confidence: 94%
See 3 more Smart Citations
“…T. thus proposed a "cross-linking" model in which the two ends of long chitin oligomers each bind a LysM-ECD to form a dimer. In a separate NMR study assisted by synthetic chemistry, N-acetyl groups of alternating sugars were found to be located on two opposite sides of the chitin chain and directly bound by the LysM-ECD (Hayafune et al, 2014). Depleting N-acetyl groups from one side of the chitin chain did not affect chitin binding to a CEBiP-ECD, but abolished dimerization.…”
Section: Ligand Binding and Oligomerization Of Prr Receptor Complexesmentioning
confidence: 94%
“…Liu et al, 2012;Hayafune et al, 2014). Two competing models have been proposed for chitin-induced dimerization of LysM-ECDs.…”
Section: Ligand Binding and Oligomerization Of Prr Receptor Complexesmentioning
confidence: 99%
See 2 more Smart Citations
“…In the situation of defence responses to pathogenic fungi, LysM RLK1 (Wan et al 2008) or CERK1 (Miya et al 2007)/CERK1 (as in Arabidopsis ) or CERK1/CEBiP receptor dimers (as in rice, Shimizu et al 2010) needs longer chito-oligomers, like octamers to activate its response through heterodimerisation (Hayafune et al 2014; Liu et al 2015). The perception of shorter oligosaccharides such as chitotetraose could instead rely on monomeric receptors (Miyata et al 2014; Shinya et al 2015) as into each receptor’s LysM domain, half of this oligomer molecule (C4) fits (Liu et al 2012; Shinya et al 2015).…”
Section: Resistance and Signalling In Plantsmentioning
confidence: 99%